Aplicación del Loan-To-Value en Latinoamérica, diferencias en implementación e impacto para el mercado del crédito inmobiliario (2020)
This paper estimate the effects of Loan-to-value application on housing credit market in five Latin-Americans countries; Colombia, Brazil, Mexico, Peru and Chile. With this objective in view this paper has a bibliographic review about the effects of Macroprudential policies and Loan-to-value application in different countries, a description of the differences in Loan-to-value application in these five countries and an econometric estimation of the Loan-to-valueþs application effects. Specifically, the author takes data from 2009 to 2019 and estimates the effects of different Loan-tovalueþs intensities grades on housing credit growth by using a fixed effects model. The results show that the Loan-to-value application has a negative effect on housing credit growth and this effect is stronger in countries where the loan-to-value policy is more intensive.